Multilevel Analysis on the Contextual Effects of Hygiene, Environmental Sanitation, and Diarrhea Prevention in Elementary School Students in Ngawi, East Java - Dian Surya Kartika; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2019)
Background: Clean and healthy behavior in school is an important factor to prevent diarrhea and improve the health status of school children. This study aimed to determine the effects of hygiene and school environmental sanitation on diarrhea prevention behavior.Subjects and Method: This was an analytic observational study with a cross-sectional design. This study was conducted in Ngawi, East Java, in October 2018. A sample of 225 elementary school students was selected randomly from 25 elementary high schools in Ngawi. The dependent variable was diarrhea prevention. The independent variables were the student